Mr. and Mrs. Bunny-- detectives extraordinaire! - Horvath, Polly; Blackall, Sophie (New York Yearling Book (Random House), 2012)
520 Middle-schooler Madeline's hippy parents have been kidnapped from Hornby Island, Canada, by foxes and Madeline, upon discovering that she can understand animal languages, hires two rabbit detectives to find them.
Originally published: New York: Schwartz & Wade Books, 2012.
730L
101277
Keywords: Human-animal communication; Kidnapping; Rabbits; Foxes; Marmots; Hippies; Mystery and detective stories -- Juvenile fiction; Hornby Island (B.C. : Island); Mystery fiction - Juvenile literature; Children's stories